Analisis Penerapan Seiri, Seiso, Seiton, Seiketsu, Shitsuke, dan Good Manufacturing Practices Unit Blow Molding PT. X - Sabila Putri Ayu Kusuma; Dwiyanti, Endang (LPPM Hang Tuah Pekanbaru, 2024)
The manufacturing industry must have competent and qualified human resources to be able to produce products that meet standards so that the company can the highest possible profit. Companies must not only be supported by adequate infrastructure, but also by a good and optimal work culture. The form of support provided is the implementation of 5S (Seiri, Seiso, Seiton, Seiketsu, Shitsuke) and GMP. (Good Manufacturing Practices). The study aims to analyze the application of 5S and GMP to the Blow Molding Unit at Company X. This is a quantitative descriptive study. The study was conducted in an observational manner aimed at observing the working environment conditions of the Blow Molding Unit directly according to the actual conditions. The research location is one of the plastic manufacturing companies that manufactures cosmetic packaging. The research was conducted in December 2023. Data collection is done by observation methods, interviews, and documentation. The results of this study show that applications with the category